Duodenal pseudomelanosis (pseudomelanosis duodeni): a rare endoscopic finding - Aloísio Felipe-Silva; Fernando Peixoto Ferraz de Campos; José Guilherme Nogueira da Silva (University of São Paulo, 2011)
Duodenal pseudomelanosis (or pseudomelanosis duodeni) is a rare benign condition characterized by black-brown speckled pigmentation of the duodenal mucosa. Collections of pigment−laden macrophages are found in the tips of duodenal villi. The pigment is thought to be mostly composed of ferrous sulfide. Histochemichal stains for iron (Perl's prussian blue) or melanin (Masson- Fontana) may be positive, but are usually negative or unpredictable. Duodenal pseudomelanosis occurs predominantly in middle-aged to old adults and more commonly in females. It is associated with chronic renal failure, arterial hypertension, diabetes mellitus and gastrointestinal bleeding. Medications such as ferrous sulfate, hydralazine, propranolol, hydrochlorothiazide and furosemide are thought to play a role as well. We report a case of a 86-year-old female who presented with a history of watery diarrhea and melena. The patient had a history of high blood pressure and ischemic stroke episodes. She was on multiple medication including hidralazine, captopril, hydrochlorthiazide and aspirin. She was dehydrated, her blood pressure was 96 × 60 mmHg and neurologic examination showed complete left hemiplegia with central VII nerve palsy. Laboratory tests showed normal serum electrolytes and renal function. Hemoglobin level was 10.7 g%. An upper endoscopy showed multiple diminutive black spots throughout the distal duodenal bulb and second portion. Histology showed multiple foci of a brown-black granular pigment inside macrophages within the tips of the villi (pseudomelanosis). Stains for iron and melanin were negative. She was treated with omeprazol, parenteral fluid replacement with saline and partial fasting. After complete recovery she was discharged for ambulatory follow up.